Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L.) Kadaluarsa dengan Pemberian Berbagai Zat Pengatur Tumbuh - Irwan Nooyo; Muhammad Nasrul (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Plant growth regulators are organic or synthetic compounds that function to regulate and stimulate plant growth, both in the vegetative and generative phases. The administration of plant growth regulators (PGRs) is an effort to provide hormones to plants for optimal growth. The purpose of this study was to determine the growth and yield of expired corn (Zea mays L.) plants after the administration of various plant growth regulators. The research using a randomized block design consisted of 10 treatments where treatment A = new seeds + Aquades, B = new seeds + 500 cc / L ZPT bean sprout extract, C = new seeds + 500cc / L ZPT young coconut water, D = new seeds + 0.2 cc / L Auxin, E = new seeds + 0.2 cc / L Gibberellin, F = expired seeds + Aquades, G = expired seeds + 500 cc / L ZPT bean sprout extract, H = expired seeds + 500 cc / L young coconut water, I = expired seeds + 0.2 cc / L Auxin, J = expired seeds + 0.2 cc / l Gibberellin. Each treatment was repeated 3 times, until 30 experimental units were obtained. Based on the results of the study, the highest plants were found in treatment I = expired seeds + 0.2 cc / L auxin at plant age 6 MST with an average of 257,667. The observation of the highest number of leaves was found in treatment I = expired seeds + 0.2 cc / L auxin at plant age 6 MST with an average of 14,530 strands, the best stem diameter was in treatment F = expired seeds + Aquades, at plant age 5 MST with an average stem diameter of 28,733, observations on the weight of the cob with husk and the best weight of the cob without husk were found in treatment F = expired seeds + Aquades with an average of 287,200 grams, and 251,533 grams, observations on the length of the best cob in treatment F = expired seeds + Aquades with an average length of 19,900 cm.